ANALISIS TREND LAPORAN KEUANGAN UNTUK MENILAI KINERJA KEUANGAN PADA DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU (DPMPTSP) KABUPATEN BULELENG: ANALISIS TREND LAPORAN KEUANGAN UNTUK MENILAI KINERJA KEUANGAN PADA DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU (DPMPTSP) KABUPATEN BULELENG - Ni Kadek Anggi Ariani, Anggi Ariani; Desak Nyoman Sri Werastuti (Universitas Pendidikan Ganesha, 2024)
The purpose of this research is to analyze trends in financial reports to assess the financial performance of the Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kabupaten Buleleng. This research uses mixed research methods. This research is a research step that combines two previously existing forms of research, namely qualitative research and quantitative research. The author examines theory by collecting data in the form of observations and documentation related to this research. Next, all the data is processed and then analyzed using an index formula which will later become a research result